Dysfunction of default mode network characterizes generalized anxiety disorder relative to social anxiety disorder and post-traumatic stress disorder - Yuan, Minlan; Liu, Bo; Yang, Biao; Dang, Wen; Xie, Hua; Lui, Su; Qiu, Changjian; Zhu, Hongru; Zhang, Wei (Journal of affective disorders, 2023)
The perseverative cognition of generalized anxiety disorder (GAD) is distinctive compared to other anxiety disorders. However, the disease-specific and shared neuropathophysiological mechanisms of GAD remain unclear. We recruited medication-free patients of GAD (N = 33), social anxiety disorder (SAD; N = 36), post-traumatic stress disorder (PTSD; N = 59), and healthy controls (HC; N = 50). All subjects underwent clinical assessments and resting-state functional magnetic resonance imaging. We compared both the amplitude low-frequency fluctuation (ALFF) and seed-based functional connectivity across the whole brain, using the significantly different regions from the ALFF analyses as seed regions, followed by post-hoc tests. We found that ALFF of the left angular gyrus (AG), left inferior parietal lobule (IPL), left precentral gyrus, left middle temporal gyrus, and left cerebellum were higher in GAD compared with SAD, PTSD and HC. This trend was further corroborated by the higher functional connectivity between left AG and bilateral IPL, left inferior temporal gyrus, and left medial prefrontal cortex (mPFC) in GAD. In addition, GAD and SAD both showed abnormally higher left AG-right insula connectivity. Significant correlations were found between anxiety symptom severity and the left AG regional activity and left AG-left mPFC connectivity. We did not compare the differences in neuroimaging between GAD and other anxiety disorders, such as panic disorder. The default mode network dysfunction may underlie the distinctive perseverative thoughts of GAD relative to other anxiety disorders, and left AG-right insula connectivity may reflect somatic anxiety of anxiety disorder spectrum. •Default mode network dysfunction may characterize the perseverative thoughts of GAD.•Significant correlation between left AG activity and anxiety symptom severity in GAD•Left AG-right insula connectivity may reflect somatic symptoms of anxiety disorders.